International Law and Order Enforcement: Police Assistance Programs and Politics in US-Brazil Relations - Priscila Villela (Revista Brasileira de Política Internacional, 2022)
Abstract Police Assistance programs have been a permanent part of US foreign policy towards Latin America, with Brazil being one of the most important beneficiaries. Throughout their history, they have been oriented according to changing agendas, from anticommunism to the war on drugs. Based on documentary sources and specialized literature, we analyze the politics of US policing in Brazil, reconstituting agendas and interests that motivated police assistance programs through the lens of critical police studies in IR. In doing so, we demonstrate that police cooperation is historically a crucial part of US-Brazil bilateral relations, despite the unfrequent prominence in the literature.